ASPEK HUKUM PENAWARAN UMUM EFEK SECARA ELEKTRONIK - Previanti, Niken (Veritas et Justitia, 2021)
The main issue discussed here, using a juridical normative method, regards the legal validity and implementation of, and legal protection given to investors, found in the Financial Services Authority Regulation No. 41/POJK.04/2020 re. Electronic Public Offering of Equity, Debt Securities and/or Syaria’ Undivided Share. Important to note is the fact that the Financial Services Authority is established by virtue of Law No. 21 of 2011 to replace and take over the functions of the Capital Market and Financial Institution Supervisory Agency and the Central Bank in regulating and supervising Indonesian Banks and Capital Markets and lastly protect consumers in the financial services industry.  Here should also mentioned the fact that the Capital Market Law (No. 8/1995) and its implementing regulations has yet to respond to how advances in information technology can be utilized to regulate-control and supervise public offering of shares or equity in the Capital Market.